Intervención artística como medio de expresión de protesta a la contaminación ambiental en la isla jambelí - Caamaño Serna, Erika Lucia (2018)
The present research project called "Artistic intervention as a means of protest expression to environmental pollution on Jambelí Island". Its purpose is to make an artistic proposal that consists of physically breaking the social environment of Jambelí with objects found in the place, this act is called Artistic intervention. This tries to use new methods that help to counteract the problem that has been arising on Jambelí Island with respect to environmental pollution, where it will be seen and compared what was not done and what can be done to obtain favorable results that can help the ecosystem to regenerate and recover. The diverse investigations reveal that the biodiversity of the Jambelí island is in danger due to the contamination of its habitad, a study mentions that to the year 1,5 million marine animals die due to this problem. One of the main objectives of this research work is to generate a closer relationship between the human being, art and nature in order to reach the act of reflection and thereby achieve that each individual change their perspective. The artistic intervention itself is a very effective expressive expression as long as it is known to be used in the correct way, with a vision, mission and explicit objective. This artistic form helps us to carry a direct message to people so that they can realize what is wrong and thus take them to the act of reflection; and thus be able to help nature and its biodiversity not only those but also future generations leaving them a legacy and can continue with this fight against environmental pollution and improve our planet. It can be said that the human race through history has passed several stages in its evolution, in its social and cultural environment where it has undergone changes in which it has led to certain things as well as to fail in others, people who see for the common welfare in their community as well as people who watch only for their own interests, which leads to the nature, our ecosystem and the biodiversity that it contains, being affected very significantly due to the abuses of some , that in a selfish way is only visualized in the present but not in the future where they will no longer be. It is for this reason that the present work is a way of saying "let's do something now" in a voice of protest, because when we are no longer there, what ethical principles we will have left those who come after us, and can live in a balanced and respectful way also to mother nature. This artistic work brought with it many reactions with regard to the problematic of Jambelí Island, nourishing the artist with many possibilities of how to make his main message understood, as well as the viewer who found a different way of expressing himself and making conscience through this artistic method. It is worth mentioning that one of the ways to contribute with a grain of sand to this fight against environmental pollution in Jambelí Island, is to go and directly confront people in a state of comfort, and begin to analyze and raise awareness of this problem very seriously. every time it is increasing and at the same time few people dare to intervene with these artistic forms in the urban and social environment of any place. In this way, this intervention "WHI? concludes with a reflexive act that can contribute to the possible solutions that are given from now on in Jambelí Island.